Amniotic Fluid Aspiration in Medicolegal Autopsies - Koç, Sermet; Özaslan, Abdi; Özaslan, İnci Alıç and Sarı, Hüseyin and Çakalır, Canser (The Bulletin of Legal Medicine, 1999)
Amniotic fluid aspiration occurs due to intrauterine anoxia. Being one of the causes of respiratory insufficiency and death in newborns, it can be diagnosed solely by histopathological examination. In the present paper, 12 cases with the diagnosis of amniotic fluid aspiration in autopsies between 1996-1997 in the mortuary section of the Council of Forensic Medicine are reevaluated from the medicolegal point of view. In the majority of the cases, delivery took place in locations other than hospitals, and the lack of medical intervention has been an important factor for the infavorable outcome of the autopsies. Findings of amniotic fluid aspiration stained with meconium were detected in four cases. Key words: Amniotic fluid aspiration, intrauterin asphyxia, Neonatal death, Medicolegal autopsy.